Case Report: Thrombopoietin receptor agonists in resistant thrombocytopenia in pregnancy: a case series and review of literature - Sayed, Gamal; ElKourashy, Sarah A.; Alnajjar, Mohammed; Mallahi, Naela Al; Fareed, Shehab (Frontiers in Hematology, 2023)
Immune thrombocytopenia (ITP) affects 0.1 to 1 per 1000 pregnancies and severe ITP, with platelet counts less than 10,000/µL, is difficult to manage. Two pregnant patients with ITP who were successfully treated with thrombopoietin receptor agonists (TPO-RA) at a tertiary institution are discussed. The first patient had chronic ITP, achieved complete remission with eltrombopag, but was resistant to intravenous immunoglobulin (IVIG) and steroids in her second pregnancy. Romiplostim was effective, and she had an uneventful cesarean section. The second patient responded well to eltrombopag at 35 weeks of gestation and had a vaginal delivery. ITP in pregnancy is managed based on clinical expertise, and TPO-RA use during pregnancy is largely from case reports. For severe ITP, eltrombopag or romiplostim from around 34 weeks can be used if other treatments fail, with a goal of achieving a platelet count of over 80,000/µL. The mother's response to medication may vary in different pregnancies. Induction of labor may be appropriate in some cases.